Pelatihan Strategi Penjualan Efektif melalui Tiktok; Kolaborasi Mahasiswa UNIGIRI dalam E-Commerce Tiktok - Aliriad, Hilmy; Setia Kuscahyaning Putri, Wahyu; Widya Priadana, Beny (Universitas Pahlawan Tuanku Tambusai, 2024)
Tiktok is becoming popular among people, including business people, as a platform used to market products and services. This is because Tiktok offers a wide potential to reach a large audience with diverse preferences and interests, thus making it one of the effective marketing tools in the digital age. The purpose of this service is to train students of Nahdlatul Ulama Giri University (UNUGIRI) in developing effective sales strategies through the Tiktok social media platform to support the success of e-commerce businesses. The population used in this study is 5th semester students who are attending entrepreneurship classes totaling 35 students. The research sample was taken from students who already had an online store on tiktok as many as 10 students. The methods used include hands-on training, group discussions, and Tiktok-based case studies. An important finding of this service is the increase in students ' understanding of the potential of marketing through Tiktok and mastering the right sales strategy to increase consumer engagement. The results of the service showed an increase in student skills in utilizing the Tiktok platform as an effective marketing tool. In conclusion, collaboration with UNUGIRI students in Tiktok e-commerce can increase the effectiveness of sales strategies and expand the reach of online businesses.